Factors influencing mortality in solid organ transplant recipients with bloodstream infection. (December 2015) - Oriol, I.; Sabé, N.; Melilli, E.; Lladó, L.; González-Costello, J.; Soldevila, L.; Carratalà, J.
Abstract: Although bloodstream infection (BSI) is a major cause of mortality after solid organ transplantation, information regarding its prognostic factors is scarce. To identify risk factors for 30-day mortality in solid organ transplant (SOT) recipients with BSI, we prospectively recorded all episodes of BSI occurring in adult SOT recipients from January 2007 to October 2014 at a university hospital. We identified 361 consecutive episodes of BSI involving 246 patients. The 30-day case-fatality rate from the onset of BSI was 11.4%. Factors independently associated with 30-day mortality in a logistic regression analysis were shock at presentation (OR 13.658; 95% CI 5.985–31.168), acute graft rejection in the previous 6 months (OR 3.681; 95% CI 1.059–12.795), and a platelet count of <50 000 × 10 9 /L (OR 3.070; 95% CI 1.173–8.038). Kidney recipients were the patients with the best prognosis (OR 0.375; 95% CI 0.156–0.900). Our findings may help to identify SOT recipients with BSI who are at the highest risk of death.